Adding value to tumor staging in head and neck cancer: The role of metabolic parameters as prognostic factors. Issue 8 (6th May 2021) - Rijo‐Cedeño, Jefferson; Mucientes, Jorge; Seijas Marcos, Sara; Romero, Jesús; Royuela, Ana; Carbonell, Sandra; Benlloch, Raquel; García‐Berrocal, José Ramón
Abstract: Background: Validated biomarkers in head and neck squamous cell carcinoma (HNSCC) are scarce. Methods: We retrospectively analyzed 62 patients with HNSCC treated with radiotherapy +/− concurrent chemotherapy. Pretreatment metabolic tumor volume (MTV) and total lesion glycolysis (TLG) were measured in a 18 F‐FDG positron emission tomography using a liver dependent standardized uptake value threshold. Cox regression analyses were performed to find associations with disease‐free survival (DFS) and overall survival (OS). Results: High values of MTV (>37 ml) were independently associated with a worse DFS (hazard ratio [HR] = 3.45; 95% confidence interval [CI], 1.52–7.84) and OS (HR = 3.27; 95% CI, 1.41–7.57). Similar results were found for high values of TLG (>247 g) for DFS (HR = 3.32; 95% CI, 1.44–7.65) and OS (HR = 3.42; 95% CI, 1.45–8.07). Conclusions: MTV and TLG can be considered as independent prognostic factors for DFS and OS in patients with HNSCC. Considering how easily obtainable they are, they may be useful for predicting clinical outcomes in these patients.